2020
DOI: 10.1371/journal.pone.0241608
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of laying-bird welfare following acaricidal treatment of a commercial flock naturally infested with the poultry red mite (Dermanyssus gallinae)

Abstract: The poultry red mite (PRM), Dermanyssus gallinae, a potential vector of pathogens to animals and humans, causes impaired bird welfare. A study investigated changes in behavioural variables, physiological biomarkers, and health parameters following acaricidal treatment of PRM infestation of laying hens on a commercial farm. Mite traps determined the challenge to 12,700 hens before and after drinking water administration of the acaricide, fluralaner (Exzolt®, 0.5 mg/kg; Weeks 0 and 1). Weekly daytime direct obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…In the current study, the finding on both farms that mite elimination or near-elimination was followed by an improvement in nighttime hen resting behaviour, reductions in preening and head shaking and, on the aviary farm, head scratching aligns with similar findings from a recent study on an enriched cage farm in Spain [ 17 ]. Similarly, the current study and the Spanish study both align with earlier work showing that PRM infestation results in increases in those stress-related behaviours and provide further confirmation of the effects of PRM infestation in reducing bird welfare [ 5 , 8 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the current study, the finding on both farms that mite elimination or near-elimination was followed by an improvement in nighttime hen resting behaviour, reductions in preening and head shaking and, on the aviary farm, head scratching aligns with similar findings from a recent study on an enriched cage farm in Spain [ 17 ]. Similarly, the current study and the Spanish study both align with earlier work showing that PRM infestation results in increases in those stress-related behaviours and provide further confirmation of the effects of PRM infestation in reducing bird welfare [ 5 , 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…Just a single mite was detected after Week 1 on the aviary farm, on which a calculation error resulted in administration of a dose rate 11% higher than recommended. As fluralaner efficacy on the free-range farm was equivalent to that on this farm, and as efficacy at the recommended dose rate has been consistently shown to approximate 100% on other layer farms, it can be concluded that this increase in dose rate did not affect the results, and there were no treatment-related adverse events [ 15 17 ]. Nonetheless, the error emphasizes the need for careful calculation of the appropriate product volume to ensure accurate delivery of the correct dose rate.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations